Predictors of Attendance and Attrition Among Participants of Vidas Activas y Familias Saludables (VALÉ), a Pediatric Weight Management Program for Latino Families. (29th May 2020) - Castro, Cindy; Jones, Margaret; Posada, Daisy; Mehlenbeck, Robyn; Gallo, Sina
Abstract: Objectives: To assess the demographic predictors of attrition and attendance among Latino children and their families participating in a family-based, culturally-adapted pediatric weight management program. Methods: Latino children, ages 5–9 with a BMI-for-age ≥85 th percentile were recruited from local schools and clinics serving low-income populations. Families met weekly as a group for ∼120 minutes for 10 consecutive weeks. The VALÉ program was designed to address nutrition, physical activity, and health behavior modification. The current analysis included data from four cohorts that participated in the VALÉ program between 2017 and 2019. Demographic variables were collected from families at baseline. Family attendance was recorded at each session and categorized (as ≤80% and >80% of sessions attended). Attrition was defined the % of participants who returned for follow-up immediately post program completion. Differences in demographics between attendance and attrition groups were compared using X 2 or T-Test and an alpha of 0.05 was used as the cutoff for significance. Results: Participants (n = 88) had an average age of 7.6 years, 66% were male, and the majority of parents were born in Central America (78% of mothers, 74% of fathers). Average household size was 5.7 with 88% reported being <185% of the federal poverty level. Overall, 18% attended >80% of all sessions and 61% returned for follow-up. Both maternal and paternal age were significantly higher for those completed >80% of sessions ( P  = 0.12 and 0.17, respectively) and returned for follow-up ( P  < 0.01 and P  = 0.05, respectively). The proportion of mothers who were employed was higher among those who completed >80% of sessions (69%) compared with those attending fewer sessions (39%, P  = 0.03). Total number of children in the household was lower among those who returned for follow-up ( P  = 0.04). Conclusions: Among a Latino sample of children and their families participating in a pediatric weight management program, maternal and paternal age, number of children in the household, and maternal employment were important predictors of either program attendance and/or attrition. Funding Sources: George Mason University, Potomac Health Foundation.